2021
DOI: 10.1177/07487304211014622
|View full text |Cite
|
Sign up to set email alerts
|

Circadian Interactomics: How Research Into Protein-Protein Interactions Beyond the Core Clock Has Influenced the Model of Circadian Timekeeping

Abstract: The circadian clock is the broadly conserved, protein-based, timekeeping mechanism that synchronizes biology to the Earth’s 24-h light-dark cycle. Studies of the mechanisms of circadian timekeeping have placed great focus on the role that individual protein-protein interactions play in the creation of the timekeeping loop. However, research has shown that clock proteins most commonly act as part of large macromolecular protein complexes to facilitate circadian control over physiology. The formation of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 152 publications
(232 reference statements)
1
6
0
Order By: Relevance
“…Regardless of the mechanism by which the negative arm imparts post-transcriptional regulation, FRQ, dPER, and hPER have extensive interactomes, with functions that range across diverse gene ontologies (Figure 4). This aligns with the large and variable interactomes that are a hallmark of negative-arm proteins throughout eukaryotic circadian clocks 23,27,31,[95][96][97][98] . In FRQ, we found that 58 interactors, more than half of which (33) were IDPs, have rhythmic proteins without corresponding rhythmic mRNA.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Regardless of the mechanism by which the negative arm imparts post-transcriptional regulation, FRQ, dPER, and hPER have extensive interactomes, with functions that range across diverse gene ontologies (Figure 4). This aligns with the large and variable interactomes that are a hallmark of negative-arm proteins throughout eukaryotic circadian clocks 23,27,31,[95][96][97][98] . In FRQ, we found that 58 interactors, more than half of which (33) were IDPs, have rhythmic proteins without corresponding rhythmic mRNA.…”
Section: Discussionsupporting
confidence: 71%
“…Beyond negative arm repression of the positive arm, the role of the negative arm in the regulation of output, if any, is not clear. What is known is that the negative arm forms a multitude of macromolecular complexes with a variety of proteins, including many that do not play a direct role in timekeeping [21][22][23][24] . This paradigm is true in the TTFL of fungal, insect, and mammalian cells, where the core negative arm proteins, FREQUENCY in fungi (FRQ) and the PERIODs in animals (PERs) have been demonstrated to have a wide array of interactors, only some of which impact core clock functions 21,23,[25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus in both plants and animals, internal body clocks can generate serially repeated organs. These types of clocks are distinct from the circadian oscillator, the biological clock found in most eukaryotes and some prokaryotes ( Mosier and Hurley, 2021 ). Circadian clocks coordinate development on daily and seasonal time scales.…”
Section: Introductionmentioning
confidence: 99%
“…This timekeeping mechanism is based on largely conserved proteins. 3 Cryptochrome-1 (Cry-1) and cryptochrome-2 (Cry-2) are mammalian proteins that belong to the family of plant blue-light receptors (cryptochromes). Cry-1 and Cry-2 are known as core clock components.…”
Section: Introductionmentioning
confidence: 99%